Long waves of urban reform: Putting the smart city in its place. Issue 5 (2nd November 2018) - Angelo, Hillary; Vormann, Boris
Abstract : This article maps urban reform movements onto 'long waves:' consistently patterned technological and economic cycles that repeat over time. Using the example of the United States, we argue that periodizing urban reform movements in this way reveals surprising similarities in different historical contexts. Across cycles, two tropes repeatedly appear: discourses of efficiency, that propose technological solutions to urban problems, and those of beauty, that turn to nature to improve social arrangements through design. Within cycles, reform discourses follow a similar pattern in each case: they roll out amidst the excitement of an emergent socio-technical paradigm, but, used as guidelines for its institutionalization, create new social problems even as they aim to remedy the old. In each wave planners and decision-makers try to out-engineer and out-design inequality (and other social problems), and each time they fail. We use this analytic to historicize the contemporary 'smart' and 'sustainable' city, arguing that it is only the latest in a series of beauty and efficiency solutions to urban problems, and its promises should be taken with more than a grain of salt.